2013
DOI: 10.5897/ajmr2012.2448
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the essential oil of Origanum glandulosum Desf against skin infections With PVL-producing Staphylococcus aureus strains in mice

Abstract: Skin and soft tissue infections (SSTI) caused by staphylococcal toxins including Panton-Valentine leukocidin (PVL) have increased these last years. Treatment of these complicated infections is often difficult. The search for new methods and new antimicrobial substances is necessary. Natural products such as essential oils appear among the possible solutions. The objective of our work was to prove the effectiveness of treatment of these infections with essential oils in vivo on Wistar rats; we have chosen the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This chemotype has never been reported for T. munbyanus before. In fact, previous studies conducted on plant samples collected in different areas of Algeria reported carvacrol (71.4 – 80.3%), carvacrol (35.2%) and thymol (18.5%), thymol (44.2%), thymol (37.7%) and p ‐cymene (14.7%), thymol (52.0 – 60.5%) and γ ‐terpinene (9.5 – 11.3%), thymol (44.2%), ( E )‐ β ‐ocimene (25.8%) and α ‐terpinene (12.3%), camphor (21.8 – 24.9%), camphene (13.5 – 17.3%) and 1,8‐cineole (11.9 – 15.7%), as the major essential oil constituents. Only in a few studies, the subspecies investigated (subsp.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…This chemotype has never been reported for T. munbyanus before. In fact, previous studies conducted on plant samples collected in different areas of Algeria reported carvacrol (71.4 – 80.3%), carvacrol (35.2%) and thymol (18.5%), thymol (44.2%), thymol (37.7%) and p ‐cymene (14.7%), thymol (52.0 – 60.5%) and γ ‐terpinene (9.5 – 11.3%), thymol (44.2%), ( E )‐ β ‐ocimene (25.8%) and α ‐terpinene (12.3%), camphor (21.8 – 24.9%), camphene (13.5 – 17.3%) and 1,8‐cineole (11.9 – 15.7%), as the major essential oil constituents. Only in a few studies, the subspecies investigated (subsp.…”
Section: Resultsmentioning
confidence: 95%
“…coloratus gave yield values of 0.2% and 0.1%, respectively, that are lower than those previously reported for the species, e.g . 6.0%, 5.1%, 3.0%, 2.8%, 2.3%, 2%, 1.8% . We assume that these differences may partially depend on a different glandular indumentum of the subsp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations